The effect of financial culture, risk management, organizational innovation on organizational performance in private higher education: Organizational resilience as mediating variable - Nugroho, Arissetyanto; Lutfiyah, Konita (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2024)
This study aims to determine the effect of financial culture, risk management, and organizational innovation on the performance of private tertiary institutions with organizational resilience as a mediating variable. The independent variables used are financial culture, risk management, and organizational innovation, while the dependent variable used is organizational performance, and the mediating variable used is organizational resilience. The method used in this study is a survey method, where data is obtained from the results of collection using a questionnaire. The population in this study were lecturers at private tertiary institutions in the LLDikti III area. The sampling technique was carried out using the proportionate stratified random sampling method. The sample in this study were 355 respondents. The analysis tool used is SmartPLS 3 with the path analysis method. The results of this study state that financial culture, risk management, and organizational innovation have a positive and significant effect on organizational resilience. Then financial culture, risk management, organizational innovation, and organizational resilience have a positive and significant effect on organizational performance. This research also shows that organizational resilience mediates the relationship between financial culture and organizational performance and also between organizational innovation and organizational performance. Meanwhile, organizational resilience failed to mediate the effect of risk management on organizational performance.